Synthesis, Characterization and Antimicrobial Activity Study of the Ternary (Poly Anthranilic acid- Graphene Oxide- Zinc Oxide) Nanocomposite - Abdulwahhab H. Majeed (Academic Science Journal)
In this study, a (Poly anthranilic acid (PANA)- Graphene Oxide (GO) nanosheets, Zinc Oxide (ZnO) nanorods) ternary nanocomposite was synthesized. The prepared compounds (PANA, GO, ZnO and the (PANA-GO-ZnO) nanocomposite were characterized through FTIR, XRD, SEM, and thermal analysis. The analyses revealed that GO consisted of nanostructures in sheet form, ZnO consisted of rod-shaped structures with dimensions varying between 39 and 63 nm, and the polymer appeared in regular, sphere-like shapes with different diameters. Thermal analyzes of the polymer showed that the polymer (PANA) partially decomposes in the temperature range (145.3-315.6 o C), and completely decomposes at (315.6, 541.9 o C), which means that the polymer is thermally stable. The ternary nanocomposite was employed to assess their efficacy against four distinct bacterial strains (Staphylococcus aurous, Staphylococcus epidermidis, Escherichia coli, and Klebsiella sp.) and one fungal strain (Candida albicans). It was also found that this compound has a high effectiveness in inhibiting the tested microorganisms.